The Model Investment Management of Cash Waqf - Masse, Rahman Ambo; Aderus, Andi (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2022)
This study aims to analyze the management of waqf through money and its implications for the development of social institutions in the Muslim community. The research departs from the phenomenon of cash waqf management in Nazhir waqf which is not in accordance with the mandate of the legislation, namely cash waqf must be managed and invested in Islamic financial institutions. This study uses a qualitative method (qualitative method) with a phenomenological approach. The data were obtained through in-depth interviews and documents on Baitul Maal Muamalat, LAWAZIS DDI, Yatim Mandiri, and LAZISNU PCNU Parepare, and the Ministry of Religion. The results showed that the form of cash waqf management at waqf institutions was in the form of waqf through money. This form of waqf is not invested in Islamic financial institutions. However, the receipt of waqf donations through cash is directly channeled to waqf programs in the form of real assets. The implications of waqf management through money on the development of social institutions are very significant. Yatim Mandiri allocates waqf through money for scholarships, and means of learning studios for the Qur'an and mathematics. Baitul Maal Muamalat allocated waqf through money for the construction of the Adetarinah mosque in Antang. LAWAZIS DDI allocates waqf through money for the construction of the DDI secretariat and the Tahfidz Institute in Makassar. LAZISNU PCNU Parepare allocates waqf through money for land acquisition and construction of facilities and infrastructure for the Zubdatul Asrar Islamic boarding school in Parepare.